1991
DOI: 10.1116/1.585361
|View full text |Cite
|
Sign up to set email alerts
|

A servo guided XY–theta stage for electron beam lithography

Abstract: This paper describes a high precision X–Y–theta stage for use inside the variable axis immersion lens of IBM’s EL3+ direct write e-beam lithography systems. X–Y stages typically use some form of rail and bearing combination to provide guidance along the X and Y axes. The planar stage presented in this paper has no X or Y guide rails or bearings, instead both guidance and positioning are provided by the simultaneous operation of three mechanical drives controlled by closed-loop velocity, position, and theta ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10 The most commonly used anisotropic etches are KOH-based. Various studies have found that the etch rate on ͕111͖ surface orientations is considerably lower than that on ͕100͖ surfaces, [11][12][13][14] sometimes by a factor of as much as 200. 11 When such an etch is applied to a ͕100͖ oriented surface, pyramidal features, referred to as hillocks, with perfect ͕111͖ faces are formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 The most commonly used anisotropic etches are KOH-based. Various studies have found that the etch rate on ͕111͖ surface orientations is considerably lower than that on ͕100͖ surfaces, [11][12][13][14] sometimes by a factor of as much as 200. 11 When such an etch is applied to a ͕100͖ oriented surface, pyramidal features, referred to as hillocks, with perfect ͕111͖ faces are formed.…”
mentioning
confidence: 99%
“…Various studies have found that the etch rate on ͕111͖ surface orientations is considerably lower than that on ͕100͖ surfaces, [11][12][13][14] sometimes by a factor of as much as 200. 11 When such an etch is applied to a ͕100͖ oriented surface, pyramidal features, referred to as hillocks, with perfect ͕111͖ faces are formed. 12,13 On arbitrarily oriented crystals, the behavior of anisotropic etches becomes more complicated.…”
mentioning
confidence: 99%